Land of wondrous cold : the race to discover Antarctica and unlock the secrets of its ice - Wood, Gillen D'Arcy (Princeton University Press, 2020)
"A history of the first race to Antarctica that weaves the great polar discoveries of the nineteenth century with scientific breakthroughs of the modern era. Antarctica, the ice kingdom hosting the South Pole, looms large in the human imagination. The secrets of this vast frozen desert have long tempted explorers, but its brutal climate and glacial shores notoriously resist human intrusion. Land of Wondrous Cold tells a gripping story of the pioneer nineteenth-century voyages, when British, French, and American commanders raced to penetrate Antarctica's glacial rim for unknown lands beyond. These intrepid Victorian explorers-James Ross, Dumont D'Urville, and Charles Wilkes-laid the foundation for our current understanding of Terra Australis Incognita. Today, the white continent poses new challenges, as scientists race to uncover Earth's climate history recorded in the south polar ice and ocean floor, and to monitor the increasing instability of the Antarctic ice cap, which threatens inundation of coastal cities worldwide. Interweaving the breakthrough research of the modern Ocean Drilling Program with the dramatic discovery tales of their Victorian-era forerunners, Gillen D'Arcy Wood describes Antarctica's role in a planetary drama of plate tectonics, climate change, and species evolution stretching back more than thirty million years. An original, multifaceted portrait of the polar continent emerges, illuminating our profound connection to Antarctica in its past, present, and future incarnations. A deep-time history of monumental scale, Land of Wondrous Cold brings the remotest of worlds within close reach-an Antarctica vital to both planetary history and human fortunes"--